Brief Report: Partial‐ and Full‐Thickness Focal Cartilage Defects Contribute Equally to Development of New Cartilage Damage in Knee Osteoarthritis: The Multicenter Osteoarthritis Study. Issue 3 (27th February 2017) - Guermazi, Ali; Hayashi, Daichi; Roemer, Frank W.; Niu, Jingbo; Quinn, Emily K.; Crema, Michel D.; Nevitt, Michael C.; Torner, James; Lewis, Cora E.; Felson, David T.
Abstract : Objective: To determine the risk of incident cartilage damage at follow‐up in subregions that are undamaged at baseline, by comparing tibiofemoral joint compartments with a baseline focal partial‐thickness or full‐thickness cartilage defect against compartments without any baseline cartilage damage, in knees with and those without radiographic osteoarthritis (OA). Methods: We included participants in the Multicenter Osteoarthritis Study for whom there were semiquantitative magnetic resonance imaging readings at baseline and at 30 months. We estimated the risk of incident cartilage defects developing in tibiofemoral compartments with prevalent partial‐thickness and full‐thickness cartilage defects in only one subregion within the compartment, using tibiofemoral compartments with no baseline cartilage defects as a referent. Logistic regression with generalized estimating equations was used for all analyses, with adjustments for confounders. Results: A total of 374 compartments (359 knees) were included, and 140 knees (39%) had radiographic OA. Compared to compartments with no baseline cartilage defects, those with partial‐thickness (adjusted odds ratio 1.62 [95% confidence interval 1.06–2.47]) and full‐thickness (adjusted odds ratio 1.92 [95% confidence interval 1.00–3.66]) cartilage defects in a subregion had a higher risk of incident cartilage defects in other subregions in the same compartment. Conclusion: Prevalent focal cartilage defects, regardless of defect depth, in a single subregion within a tibiofemoral joint compartment increase the risk of developing new cartilage damage in other subregions of the same compartment for middle‐aged to elderly persons with or at high risk of knee OA.